Figures of pedagogy in Ama Ata Aidoo’s Changes and Buchi Emecheta’s Double Yoke - Angela M. Fubara (Tydskrif vir Letterkunde, 2017)
Writers and critics of women emancipation have lifted and advanced the struggle to another phase. The last decade has witnessed feminist writing from female disparagement, subjugation, women as victims craving to be fulfilled wives and mothers endowed with “pretty faces and fertile ova” (Chukwuma), to women striving for empowerment and assertion. A revisit of Buchi Emecheta’s Double Yoke and Ama Ata Aidoo’s Changes reveals that these inimitable feminist writers, while depicting the women in the abyss of debasement in patriarchal society portray assertive heroines teaching by precepts immanent in pedagogical assets. Economic independence and education are added advantages to factors that make for self-assertion. Self-assertion, seen as a woman’s greatest weapon, serves as a pedagogical instrument for equipping both sexes. This article focuses on narrative strategies that evoke images that go beyond women disparagement and marginalisation to female empowerment and selfassertion through close rereadings of Emecheta’s and Aidoo’s novels.